PROFIL KEMAMPUAN DASAR MATEMATIKA SISWA SMP KELAS VIII - Natsir, Irmawaty; Suryani, Dessy Rizki; Nur'aini, Khumaeroh Dwi (Jurnal Pendidikan Matematika Unpatti, 2023)
This research was conducted with the aim of describing the profile of the basic mathematical abilities of grade VIII junior high school students. The type of research used is descriptive qualitative with the subject of class VIII students at one of the State Middle Schools in Merauke, totaling 33 students. The data collection instrument used basic mathematics ability test questions which totaled 20 multiple choice questions. To analyze the data obtained, the steps consisting of data reduction, data presentation, and drawing conclusions were used using Miles and Huberman's analysis techniques. The results of the study showed that the basic math abilities of grade VIII students were moderate. With the highest basic mathematical abilities in the elements of numbers and the lowest in elements of geometry